Gender dalam Perspektif Pendidikan Islam - Syarifuddin Ondeng; Syahruddin Usman; Rofiqah Al Munawwarah (Vifada Journal of Education, 2023)
This article discusses the concept of gender in an Islamic perspective and analyzes gender issues that often arise. The problem of Islamic education that is often highlighted by the West is the issue of gender equality and the role and participation of women in education among Muslims. The issue of gender equality in the field of education, then raises various criticisms of Islamic teachings which are considered not to provide space for women in the world of education, because most of the teachings of Islam are considered too masculine and in favor of men. This article concludes that the concept of gender in Islam is based on the principle of equality in value and dignity, with recognition of differences in roles and balanced responsibilities. Although there are differences in interpretation among Islamic scholars and thinkers, the essence of Islamic teachings emphasizes respect for the rights and roles of both sexes in society. Issues in gender are gender equality and gender injustice